Synthesis of Ultrathin 2D Nonlayered α‐MnSe Nanosheets, MnSe/WS2 Heterojunction for High‐Performance Photodetectors. Issue 8 (8th July 2021) - Zhang, Zucheng; Zhao, Bei; Shen, Dingyi; Tao, Quanyang; Li, Bo; Wu, Ruixia; Li, Bailing; Yang, Xiangdong; Li, Jia; Song, Rong; Zhang, Hongmei; Huang, Ziwei; et al.
Abstract : Numerous efforts have been made to synthesize 2D atomic semiconductor materials and their heterojunctions because of the diverse novel properties and potential applications in constructing next‐generation highly compact electronic and optoelectronic devices. However, intrinsic 2D p‐type semiconductor materials are still scarce. Herein, to enrich the p‐type 2D semiconductor family, epitaxial growth of a large‐area, ultrathin 2D nonlayered p‐type semiconductor α‐MnSe on mica with the thickness down to one unit crystal cell (0.9 nm) is reported. Moreover, the thickness of the α‐MnSe nanosheets can be systematically tailored from over 150 to 0.9 nm by increasing the flow rate of the carrier gas. X‐ray‐diffraction, transmission electron microscopy, and electron diffraction studies confirm that the resulting 2D nanosheets are high‐quality single crystals. The photodetector based on the p‐type α‐MnSe nanosheet shows a fast response time of 4 ms. Furthermore, α‐MnSe/WS2 heterojunctions are synthesized and a diode based on p‐type α‐MnSe and n‐type WS2 displays outstanding photodetectivity (1.00 × 10 13 Jones), high photoresponsivity (49.1 A W −1 ), and an obvious rectification ratio (283). Together, the synthesis of α‐MnSe and the α‐MnSe/WS2 p–n heterojunction provides opportunities for next‐generation electronics and optoelectronics. Abstract : Ultrathin nonlayered α‐MnSe nanosheets are successfully synthesized on mica. The thickness of the α‐MnSe nanosheets can be systematically tailored from over 150 to 0.9 nm by modulating the growth conditions. A photodetector made from an α‐MnSe nanosheet displays ultrafast photoresponse speed. Moreover, the α‐MnSe/WS2 p–n diode shows outstanding photodetectivity and high photoresponsvity.